Connecting the Dots : People, Jobs, and Social Services in Urban Ghana - Arroyo-Arroyo, Fatima (Washington, DC: World Bank, 2021)
Major Ghanaian cities are at a critical point that will determine whether they become an engine of or a burden on the country’s development. Ghana’s urban areas contribute to more than two-thirds of the country’s gross national product, and cities will continue to grow rapidly, especially those other than capital cities. Intermediary cities such as Kumasi and Tamale are expected to double their populations by 2030, demonstrating both their importance and their potential for contributing further to economic growth. However, if nothing is done to change the current trends, the cost of congestion and externalities will outweigh any productivity benefits the cities can deliver. Connecting the Dots: People, Jobs, and Social Services in Urban Ghana aims to assess the constraints to accessing jobs and social services in Ghanaian cities, especially those faced by women, low-income groups, people with disabilities, and children, and proposes a path to transform urban mobility and public transport. The report focuses on two intermediary cities—Kumasi and Tamale—as well as on the Greater Accra region. It includes a comprehensive analysis of mobility and accessibility issues and recommends a programmatic phased approach to address these issues. Finally, in the context of COVID-19 (coronavirus), the report analyzes not only major challenges for the urban transport sector, but also opportunities to rethink the role of urban mobility for more inclusive and sustainable growth.